The Role of Job Satisfaction and Transformational Leadership on Organizational Culture - Sri Hartati; Herni Utami Rahmawati; Amin Budiastuti; Rosalina Anindia Sari Kartika; Nurul Hasanah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study explores the relationships between Job Satisfaction, Transformational Leadership, and Organizational Culture in private companies. By employing a quantitative research methodology, data was gathered from a sample of 105 employees through a purposive sampling technique to ensure a representative cross-section of the target population. The collected data were then analyzed using Partial Least Squares (PLS) regression, facilitated by SmartPLS version 3.29. The study's findings reveal that both Job Satisfaction and Transformational Leadership have a significant positive influence on the development of Organizational Culture within private sector organizations. Specifically, the results suggest that the role of leadership in shaping organizational values and fostering employee satisfaction plays a crucial part in strengthening the cultural foundation of a company. These insights emphasize that private companies should not solely focus on individual performance or leadership traits but also devote efforts to cultivating a robust organizational culture that aligns with the overall strategic objectives. The research provides valuable implications for companies seeking to enhance organizational performance by focusing on a more holistic approach to management and leadership development.